Implementation of a Quality Improvement Tool “Recover25” to Guide the Care of Patients Experiencing Prolonged Critical Illness: A Mixed-Method Feasibility Study - Laura Allum, MRes; Leah Homden, BSc; Nicholas Hart, PhD; Bronwen Connolly, PhD; Natalie Pattison, PhD; Louise Rose, PhD (Critical Care Explorations)
OBJECTIVES:. Few quality improvement (QI) tools are specifically designed to manage the care of patients experiencing prolonged critical illness. This risks omissions in care. To determine the implementation feasibility and clinician acceptability of our QI tool “Recover25,” we focused on actionable processes of care for patients with an ICU stay of over 7 days and their families. DESIGN:. Parallel convergent mixed-methods feasibility study conducted between February 2024 and May 2024. SETTING:. A mixed ICU in London, United Kingdom. SUBJECTS:. Patients with an ICU stay of more than 7 days, and the staff who care for them. INTERVENTIONS:. We invited representatives of all ICU professions to a weekly QI round. MEASUREMENTS AND MAIN RESULTS:. We recorded the time completed Recover25, the amount and type of actions generated following Recover25 use (i.e., what new care activities did it prompt), and the number and profession of staff attending each round. We administered the Theoretical Framework of Acceptability (TFA) questionnaire and conducted semi-structured clinician interviews. We calculated means (sds) or interquartile ranges (IQRs) (percentiles) of time to complete and a number of actions generated. We analyzed and integrated qualitative data using framework analysis informed by the TFA. “Recover 25” was used 34 times (65%) of 52 opportunities with 26 patients. Median (IQR) Recover25 completion time was 9.75 minutes (8.2–14.9 min) with a completion rate of 96% (89–100%). Recover25 usage prompted a median of 1 (IQR) (1–2) new action. There was a mean of 4 (sd 2) interprofessional team members attending each QI round. Nineteen clinicians completed 33 TFA questionnaires and 11 interviews. Recover25 was perceived as acceptable, with 94% reporting it aligned with their principles of good care, 85% perceiving it as a coherent intervention, and 67% perceiving it was effective. Interview data showed participants valued the emphasis on person-centered care and highlighted ways to improve implementation. CONCLUSION:. Recover25 was perceived as feasible to implement and acceptable by staff. Further work is needed to understand the effects on patient experience and outcomes.